2016
DOI: 10.1016/j.bbrc.2016.01.092
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic activity of jiadifenolide on neuronal precursor cells derived from human induced pluripotent stem cells

Abstract: Although jiadifenolide has been reported to neurotrophin-like activity in primary cultured rat cortical neurons, it is unknown on that of activity in human neurons. Thus, we aimed to assess neurotrophin-like activity by jiadifenolide in human neuronal cells. We analyzed neuronal precursor cells derived from human induced pluripotent stem cells for microtuble-associated-protein-2 expression by immunofluorescence and western blot, following jiadifenolide treatment. Jiadifenolide promoted dendrite outgrowth, faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…We first validated the biological activity of a natural illicium sesquiterpene (synthetic Jiadifenolide 3 ) in this model, and found that it potently enhanced serum deprivation‐induced neurite outgrowth (140 % compared to DMSO), with the strongest effect at a concentration of 1000 n m ( Figure and other data not shown). This magnitude of neurite outgrowth stimulation is comparable to the effects of other neurotrophic agents on N2a cells, as well as the effects of Jiadifenolide in other neurotrophic assays . It is noteworthy that N2a cells are not responsive to classical neurotrophins such as BDNF, suggesting that the neurotrophic effect of Jiadifenolide is independent of these mechanisms.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…We first validated the biological activity of a natural illicium sesquiterpene (synthetic Jiadifenolide 3 ) in this model, and found that it potently enhanced serum deprivation‐induced neurite outgrowth (140 % compared to DMSO), with the strongest effect at a concentration of 1000 n m ( Figure and other data not shown). This magnitude of neurite outgrowth stimulation is comparable to the effects of other neurotrophic agents on N2a cells, as well as the effects of Jiadifenolide in other neurotrophic assays . It is noteworthy that N2a cells are not responsive to classical neurotrophins such as BDNF, suggesting that the neurotrophic effect of Jiadifenolide is independent of these mechanisms.…”
Section: Resultssupporting
confidence: 67%
“…To investigate their activity profiles, we analyzed the effects of the prepared compounds on neuronal cells. Previous studies have shown that natural products of the illicium family and their structural analogues are capable of promoting NGF‐mediated neurite outgrowth in neuronal cells (rat PC12 cells and primary cell cultures) . To explore the scope and species‐ independence of the neurotrophic activity of illicium sesqui terpenes in the present study, we used mouse N2a cells, an established model for neurite outgrowth .…”
Section: Resultsmentioning
confidence: 99%
“…until day 27 p.i. At the end of treatment, mice were euthanized and the CNS tissue was collected and analyzed for the expression of microtubule-associated protein 2 (MAP2), which is specifically expressed in dendrites and plays a key role in dendritic outgrowth, branching and synaptogenesis202122. Our data show that FSD-C10 increased MAP2 expression and improved MAP2 positive dendritic morphology in prefrontal cortex and hippocampus compared to tissue from untreated EAE mice (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Human embryonic stem cells (hESCs), and human induced pluripotent stem cells (hiPSCs) can differentiate into varous types of cells found in human organs, such as the brain, liver, heart, pancreas, lung, and the small intestine [ 1 7 ]. As hESCs are associated with several ethical issues, hiPSCs are now expected to be a valuable tool for predicting the clinical safety and efficacy of drug candidates, or for clinical application of regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…As hESCs are associated with several ethical issues, hiPSCs are now expected to be a valuable tool for predicting the clinical safety and efficacy of drug candidates, or for clinical application of regenerative medicine. Undifferentiated hiPSCs can be induced to differentiate into the three principal germ cell layers, ectoderm, mesoderm, and definitive endoderm (DE), by different methods, thereby forming the various cells of human organs [ 1 , 4 , 7 ]. Thus, to obtain a large number of organ-specific differentiated cells from hiPSCs, it is important to maintain the proper undifferentiated state of the hiPSCs and to induce their efficient differentiation into the three principal germ layers.…”
Section: Introductionmentioning
confidence: 99%